Missed opportunities for diagnosis of female genital mutilation. Issue 3 (5th March 2014) - Abdulcadir, Jasmine; Dugerdil, Adeline; Boulvain, Michel; Yaron, Michal; Margairaz, Christiane; Irion, Olivier; Petignat, Patrick
Abstract: Objective: To investigate missed opportunities for diagnosing female genital mutilation (FGM) at an obstetrics and gynecology (OB/GYN) department in Switzerland. Methods: In a retrospective study, we included 129 consecutive women with FGM who attended the FGM outpatient clinic at the Department of Gynecology and Obstetrics at the University Hospitals of Geneva between 2010 and 2012. The medical files of all women who had undergone at least 1 previous gynecologic exam performed by an OB/GYN doctor or a midwife at the study institution were reviewed. The type of FGM reported in the files was considered correct if it corresponded to that reported by the specialized gynecologist at the FGM clinic, according to WHO classification. Results: In 48 (37.2%) cases, FGM was not mentioned in the medical file. In 34 (26.4%) women, the diagnosis was correct. FGM was identified but erroneously classified in 28 (21.7%) cases. There were no factors (women's characteristics or FGM type) associated with missed diagnosis. Conclusion: Opportunities to identify FGM are frequently missed. Measures should be taken to improve FGM diagnosis and care.